Program Mentoring Dalam Kasus Penempatan Tenaga Kerja Bermasalah Di Perpustakaan - Sujoko, Sujoko (STAIN Ponorogo, 2015)
Mentoring program for misplacing workers at libraries dealts with the programs to to organize people in order to they can adjust of work rhythm in the library. This study is a part of human resources management, making mentee (member of programs) to be independent, not dependent, and can contribute to the library. This program can be applied for same cases in the future.